Senegal : Third Review Under the Policy Support Instrument and First Review and Augmentation of Access Under the Exogenous Shocks Facility; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Senegal. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper presents key findings of the Third Review under the Policy Support Instrument (PSI) for Senegal. The budgetary slippages, which had seriously affected the economy and put Senegal's PSI-supported program at risk, have been successfully addressed. In line with program commitments, the government's unpaid bills have been substantially reduced and far-reaching public financial management reforms launched. A temporary fiscal easing relative to earlier program targets is envisaged for 2009 to help counter the impact of the external shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet